Flexible stretchable alternating current electroluminescent device and preparation method thereof
Through electrospinning technology, polymers and nanoparticles are combined to prepare nanofiber membranes, combined with liquid metal and silver nanowire electrodes to form flexible stretchable alternating electroluminescent devices, solving the problems of large thickness and poor tensile performance of traditional devices, realizing the Improve the stability and adaptability of the device and expand the scope of application.
Patent Information
- Application Number
- CN202411342773.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional wearable electronic products lack flexibility, flexibility and breathability, making them difficult to adapt to changes in the dynamic curve of the human body. The substrate of existing AC electroluminescent devices is separated from the luminescent layer, resulting in large thickness and poor tensile performance, limiting their application. scope.
Electrostatic spinning technology is used to combine elastic polymer with functional nanoparticles to prepare nanofiber membranes. As the substrate of the alternating electroluminescent device and the luminescent layer is combined into one. Combining liquid metal and silver nanowire electrodes, flexible is formed through the PDMS encapsulation layer. Tensile AC electroluminescent devices.
It achieves good tensile performance, stability and mechanical strength of the device, reduces the overall thickness, adapts to changes in the human body curve, expands the application range, and maintains stable luminous performance in extreme environments.
Smart Images

Figure CN119255679A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible wearable electronic devices, and specifically relates to a flexible stretchable alternating current electroluminescent device and a preparation method thereof. Background Art
[0002] As humans enter the information age, people have higher and higher requirements for the comfort, versatility and aesthetic value of wearable electronic products. However, traditional wearable electronic products lack flexibility, softness and breathability, and are not suitable for long-term use. In contrast, flexible wearable displays are more in line with the dynamic curves of the human body and have broader application prospects, becoming a hot topic in current research. Electroluminescent textiles are one of the important components of wearable electronic products and have great research and use value. It combines light-emitting devices with fibers or textiles, and controls light intensity, color, etc. through external controllers or external environmental stimuli. It can be applied to fields such as human-computer interaction, health care and interior design.
[0003] Among electroluminescent textiles, AC electroluminescent devices (ACEL) have become one of the current research hotspots. Flexible / stretchable AC electroluminescent (ACEL) devices have the characteristics of good flexibility, high mechanical strength and high mechanical stability. They are an indispensable component of future wearable integrated device systems, have great use value and commercial prospects, and have attracted the interest of many scientific researchers. Stretchable AC electroluminescent devices refer to devices that still have normal luminous display or sensing functions under external forces such as bending, twisting, and folding. Compared with traditional display devices, they have the advantages of being light and thin, soft, stable in function, simple in manufacturing process, and easy to expand over a large area. They are the key to flexible electronic display devices having stable visual information display and high-performance lighting functions, and have very broad application prospects in the fields of stretchable light sources / displays, soft robots, and artificial electronic skin.
[0004] In recent years, electrospinning technology has been widely used for its large specific surface area, high porosity, good mechanical flexibility, simple and efficient preparation methods to produce electrospun membranes. Most polymer materials can be electrospun into nanofibers, and various other forms of materials including metals, carbon materials and ceramic nanoparticles can also be electrospun in combination with suitable polymers. In the field of optoelectronics, electrospinning has been used for transparent electrodes, functional light-emitting layers, and dielectric layers that provide optical and mechanical properties. However, only a few works involve the use of electrospinning to combine the substrate and light-emitting layer of ACEL devices into one. In addition, the nanofiber structure can enhance the mechanical flexibility of the overall device, which can open up new prospects in wearable electronic devices and large-area display applications. Summary of the invention
[0005] The present invention provides a flexible and stretchable alternating current electroluminescent device, which has both flexibility and wearable display functions and also has excellent stretchability.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A method for preparing a flexible and stretchable AC electroluminescent device, wherein the electroluminescent device comprises, from bottom to top, a bottom electrode, a light-emitting layer, a silver nanowire top electrode, and a PDMS encapsulation layer encapsulating the bottom electrode, the light-emitting layer, and the silver nanowire top electrode, the method comprising the following steps:
[0008] S1 electrospinning to prepare a luminescent layer fiber membrane: dissolving an elastic polymer in an appropriate amount of an organic solvent, adding luminescent powder and barium titanate, stirring evenly to obtain a spinning solution, and using the spinning solution to electrospin to obtain a fiber membrane with a thickness of 100-200 μm, the fiber membrane is used as the luminescent layer of the device;
[0009] Based on the total weight of the spinning solution being 100%, the content of the barium titanate nanoparticles in the spinning solution is 5%-7%, the content of the luminescent powder is 15%-35%, the content of the polymer is 15-20%, and the balance is an organic solvent;
[0010] S2 mask production: Design the luminous pattern on the computer and cut it with a plotter to obtain the mask for coating and printing the liquid metal bottom electrode;
[0011] S3: Preparation of patterned liquid metal bottom electrode: attaching a mask to the light-emitting layer prepared in S1, and coating liquid metal on the surface of the light-emitting layer not covered by the mask to form a patterned liquid metal bottom electrode;
[0012] S4: spray-printing silver nanowire top electrode: spray silver nanowire dispersion evenly on the side of the light-emitting layer prepared in S1 that is not coated with liquid metal, and dry it at room temperature to form a transparent top electrode;
[0013] S5 device encapsulation: Use transparent PDMS solution to evenly spray on the top and bottom of the device for encapsulation to obtain a flexible and stretchable alternating current electroluminescent (ACEL) device.
[0014] The present invention utilizes electrostatic spinning technology to compound elastic polymers with functional nanoparticles (luminescent powders such as ZnS:Cu and BaTiO3) to obtain an elastic nanofiber membrane, which combines the substrate and the luminescent layer of the ACEL device into one. Compared with traditional ACEL devices, the device thickness is greatly reduced and the device is endowed with good tensile properties. The method of the present invention has a simple preparation process and is easy to realize industrial mass production. The prepared luminescent device has good tensile properties, can be washed, bent, and folded, and can better fit the changes in human body curves under dynamic stretching.
[0015] Preferably, based on the total weight of the spinning solution being 100%, the content of barium titanate nanoparticles in the spinning solution is 5%-7%, the content of the luminescent powder is 21.7%-32%, the content of the polymer is 15-20%, and the balance is the organic solvent; the best choice is that the content of the luminescent powder is 21.7%-27%. The content of barium titanate nanoparticles is selected to be 5%-7% because a decrease in the content of barium titanate will lead to a decrease in the dielectric properties of the luminescent layer, and an excessive content of barium titanate will lead to agglomeration of the spinning solution.
[0016] Preferably, in S1, the conditions for electrospinning are: the spinning propulsion speed is 1.5 mL / h, the distance from the needle tip to the receiving roller is 10 cm, and the spinning voltage is 8-12 kV.
[0017] Preferably, in S1, the elastic polymer is selected from one or more of polyurethane (TPU), styrene (SBS), polydimethylsiloxane (PDMS) or polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP);
[0018] The luminescent powder is selected from one of the metal sulfide luminescent powders ZnS, CaS, SrS, CaGa2S4, SrGa2S4, and (Zn, Cd)S:Cu.
[0019] Preferably, in S1, the organic solvent is selected from one of N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) or a mixture of both. Preferably, the organic solvent is a mixture of N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) in a mass ratio of 1:1.
[0020] Preferably, in S2, the mask is a cardboard without primer, which will not damage the spun TPU composite nanofiber membrane.
[0021] Preferably, in S3, the liquid metal is one or more of gallium-indium alloy, gallium-tin alloy, gallium-indium-tin alloy, gallium-zinc alloy, gallium-rubidium alloy or gallium-cesium alloy.
[0022] Preferably, in S1, the thickness of the light-emitting layer is 160 μm±10 μm.
[0023] A flexible and stretchable alternating current electroluminescent (ACEL) device prepared according to the preparation method of the present invention.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. Compared with other materials and methods, the TPU nanofiber membrane prepared by electrospinning has better stretchability, giving the device an elastic base, which helps to fit the dynamic body curve changes of the wearer, especially in applications such as wearable devices and electronic skin. Compared with ACEL devices prepared by solution curing process, the ACEL device prepared by the present invention does not require light, heat or other conditions for initiation.
[0026] 2. The present invention prepares a substrate-free ACEL device with an overall thickness of less than 200 μm. Compared with the prior art, the device thickness is greatly reduced while ensuring that the device can work stably, thereby expanding the application range of the ACEL device.
[0027] 3. The ACEL device prepared by the present invention has good stability. The device can still emit light stably under the double 85 test (85°C temperature and 85% humidity), which not only retains the advantage of the high specific surface area of the nanofiber membrane (i.e., increases the contact area between the bottom electrode and the top electrode on the surface of the light-emitting layer), but also overcomes the structural instability caused by it; it can still work stably under a tensile strain of less than 30% and 800 cycles of stretching, and the brightness drops to 86.2% of the initial value, verifying the good mechanical stability of the ACEL device. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the device structure and some SEM images (the SEM image is omitted because the PDMS layer is a transparent material and it is difficult to scan the SEM image);
[0029] Figure 2 Brightness test of ACEL devices with different thickness of light-emitting layers in Examples 1-3;
[0030] Figure 3 This is the test of the brightness of ACEL devices with different luminescent powder contents in Examples 4-7;
[0031] Figure 4 To supplement the stress-strain test of the luminescent layer with different luminescent powder contents in Example 1;
[0032] Figure 5 To supplement the rheological test of spinning solutions with luminescent powder contents of 15.6% and 31.6% (based on the total weight of the spinning solution as 100%) in Example 2;
[0033] Figure 6 To supplement Examples 1 and 3, stress-strain tests comparing electrospinning and thermal curing processes were performed;
[0034] Figure 7 This is a comparison diagram of the unstretched and stretched ACEL device prepared in Example 6;
[0035] Figure 8This is a brightness test chart of the ACEL device prepared in Example 6 after repeated stretching 800 times under 30% tensile deformation;
[0036] Fig. 9 This is a graph showing the brightness change of the ACEL device prepared in Example 6 under a double 85 (85°C temperature and 85% humidity) environment for 72 hours;
[0037] Fig.10 This is a schematic diagram of encapsulating an ACEL device in elastic yoga clothing according to Example 8. DETAILED DESCRIPTION
[0038] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0039] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0040] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not indicated in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, if not otherwise specified, can all be obtained from commercial channels).
[0041] Eutectic gallium indium (EGaIn) was purchased from Suzhou Chuanmao Metal Materials Co., Ltd.;
[0042] PDMS, purchased from Dow Corning Silicones, USA;
[0043] ZnS:Cu luminescent powder was purchased from Shanghai Keyan Optoelectronic Technology Co., Ltd.;
[0044] Silver nanowires were purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.
[0045] In the following examples, the conditions for electrospinning are: the spinning propulsion speed is 1.5 mL / h, the distance from the needle tip to the receiving roller is 10 cm, and the spinning voltage is 8-12 kV.
[0046] Example 1
[0047] A method for preparing a flexible and stretchable AC electroluminescent device, the specific steps are as follows:
[0048] S1 Preparation of luminescent layer fiber membrane by electrospinning: Dissolve TPU particles in an organic solvent mixed with N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) (the mass ratio of DMF to THF is 1:1, the same below), and stir for 12 hours. Add luminescent powder and barium titanate nanoparticles, stir evenly to obtain spinning solution.
[0049] Taking the total weight of the spinning solution as 100%, the content of barium titanate nanoparticles in the spinning solution is 6.02%, the content of the luminescent powder is 18.8%, the content of the TPU particles is 18.8%, and the remainder is an organic solvent with a mass ratio of DMF to THF of 1:1.
[0050] The spinning solution is used for electrostatic spinning to obtain a fiber membrane with a thickness of 100 μm.
[0051] S2 mask production: Design the luminous pattern on the computer and cut it with a plotter to obtain the mask for coating and printing the liquid metal bottom electrode;
[0052] S3: Preparation of patterned liquid metal bottom electrode: attaching a mask to the light-emitting layer prepared in S1, coating liquid metal (eutectic gallium indium (EGaIn), the same below) on the surface of the light-emitting layer not covered by the mask, to form a patterned liquid metal bottom electrode;
[0053] S4: spray-printing silver nanowire top electrode: spray silver nanowire dispersion evenly on the side of the light-emitting layer prepared in S1 that is not coated with liquid metal, and dry it at room temperature to form a transparent top electrode;
[0054] S5 device encapsulation: Use transparent PDMS solution to evenly spray on the top and bottom of the device for encapsulation to obtain a flexible and stretchable alternating current electroluminescent (ACEL) device.
[0055] Example 2
[0056] A method for preparing a flexible and stretchable AC electroluminescent device, the specific method is the same as that in Example 1, except that:
[0057] The spinning solution was used for electrostatic spinning and the spinning time was controlled to obtain a fiber membrane with a thickness of 160 μm.
[0058] Example 3
[0059] A method for preparing a flexible and stretchable AC electroluminescent device, the specific method is the same as that in Example 1, except that:
[0060] The spinning solution was used for electrostatic spinning and the spinning time was controlled to obtain a fiber membrane with a thickness of 190 μm.
[0061] Embodiment 4-7
[0062] A method for preparing a flexible and stretchable AC electroluminescent device, the specific steps are as follows:
[0063] S1 Preparation of luminous layer fiber membrane by electrospinning: TPU particles were dissolved in an organic solvent mixed with N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) (the mass ratio of DMF to THF was 1:1, the same below), stirred for 12 hours, luminescent powder and barium titanate nanoparticles were added, and the spinning solution was obtained after stirring evenly. The spinning solution was used for electrospinning to obtain a fiber membrane with a thickness of 160 μm.
[0064] Taking the total weight of the spinning solution as 100%, the formula of each component in the spinning solution is shown in Table 1.
[0065] Table 1
[0066] Example 4 Example 5 Example 6 Example 7 Luminous powder / % 15.6% 21.7% 27% 31.6% TPU particles / % 18.8% 18.1% 16.9% 15.8% Barium titanate nanoparticles / % 6.25% 5.80% 5.41% 5.06% The balance is organic solvent 59.35% 54.4% 50.7% 47.54% Total weight of spinning solution / % 100% 100% 100% 100%
[0067] S2 mask production: Design the luminous pattern on the computer and cut it with a plotter to obtain the mask for coating and printing the liquid metal bottom electrode;
[0068] S3: Preparation of patterned liquid metal bottom electrode: attaching a mask to the light-emitting layer prepared in S1, coating liquid metal on the surface of the light-emitting layer not covered by the mask, to form a patterned liquid metal bottom electrode;
[0069] S4: spray-printing silver nanowire top electrode: spray silver nanowire dispersion evenly on the side of the light-emitting layer prepared in S1 that is not coated with liquid metal, and dry it at room temperature to form a transparent top electrode;
[0070] S5 device encapsulation: Use transparent PDMS solution to evenly spray on the top and bottom of the device for encapsulation to obtain a flexible and stretchable alternating current electroluminescent (ACEL) device.
[0071] Supplementary Example 1 Stress-strain test of the luminescent layer fiber membrane prepared by electrospinning
[0072] The light-emitting layer film prepared in S1 of Example 4-7 was subjected to stress-strain test, and the specific implementation steps were as follows:
[0073] 1. Cut the light-emitting layer film prepared in Example 4-7 into strips with a length of 4 cm and a width of 1 cm;
[0074] 2. Cut A4 printing paper into several hollow paper pieces with an outer length of 4 cm and an inner length of 3 cm, and then sandwich the long strips prepared in step 1 between two hollow paper pieces to obtain stress-strain test samples.
[0075] Supplementary Example 2 Rheological Test
[0076] The spinning solutions prepared in S1 of Example 4 and Example 7 were subjected to rheological tests.
[0077] Comparative Example 1
[0078] S1 Preparation of curing precursor polymer:
[0079] The precursor polymer is solidified, and the formula is the same as the spinning solution in Example 4.
[0080] S2 thermal curing process to prepare the light-emitting layer: The cured precursor polymer prepared in S1 was evenly brushed on the glass plane, and the brushing thickness was controlled to be 160 μm. It was placed in an 80°C forced air oven for 30 minutes to finally prepare the light-emitting layer of the thermal curing process.
[0081] Supplementary Example 3 Stress and strain test of the light-emitting layer film prepared by thermal curing process
[0082] The stress-strain test was performed on the light-emitting layer film prepared in Comparative Example 1, and the specific implementation steps are as follows:
[0083] 1. The light-emitting layer film prepared in Comparative Example 1 was cut into strips with a length of 4 cm and a width of 1 cm;
[0084] 2. Cut A4 printing paper into several hollow paper pieces with an outer length of 4 cm and an inner length of 3 cm, and then sandwich the long strips prepared in step 1 between two hollow paper pieces to obtain stress-strain test samples.
[0085] Example 8 Application of ACEL device packaging on elastic yoga clothing
[0086] A method for preparing a flexible and stretchable AC electroluminescent device, the specific steps are as follows:
[0087] S1-S4 are the same as in Example 6;
[0088] S5 device packaging: Use transparent PDMS solution to evenly spray on the top and bottom of the device for packaging. When the PDMS solution at the bottom has not yet solidified, transfer the device to the elastic yoga clothing to obtain a wearable, flexible and stretchable alternating current electroluminescent (ACEL) device.
[0089] The ACEL device prepared in this embodiment needs to use a small driver to drive the ACEL device to emit light. The above test results are analyzed as follows:
[0090] Attached Figure 1 The schematic diagram of the device structure and some SEM images (the SEM images are difficult to scan because the PDMS layer is a transparent material), from top to bottom are the PDMS encapsulation layer (for illustration only), the top electrode AgNWs, the light-emitting layer, and the bottom electrode liquid metal. When the product is prepared, the PDMS encapsulation layer encapsulates the bottom electrode, the light-emitting layer, and the silver nanowire top electrode.
[0091] Attached Figure 2 The effect of different thicknesses of the light-emitting layer (Examples 1-3) on the brightness of the ACEL device was tested. When the thickness of the light-emitting layer is below 100μm, the bottom electrode and the top electrode of the device are very likely to come into contact, causing the device to short-circuit and fail to emit light; when the thickness of the light-emitting layer is 100μm, the device is prone to local breakdown, resulting in uneven overall light emission; then, when the thickness of the light-emitting layer increases to 160μm, the brightness and working stability of the device are both good; when the thickness of the light-emitting layer increases to more than 190μm, the brightness of the device decreases sharply. Therefore, the best choice of the light-emitting layer thickness is 160μm±10μm.
[0092] Attached Figure 3 The effects of different luminescent powder contents (Examples 4-7) in the spinning solution on the brightness of the ACEL device were tested. As the luminescent powder content increased, the brightness of the device increased. When the luminescent powder content in the spinning solution was greater than 27%, the brightness of the device increased slowly. Therefore, the luminescent powder content in the spinning solution is preferably 21.7%-32%.
[0093] Attached Figure 4 The stress-strain of the luminescent layer with different luminescent powder contents was tested (Supplementary Example 1). As the luminescent powder content in the spinning solution increased, the stress-strain performance of the luminescent layer decreased. When the luminescent powder content increased to 31.6% (based on the total weight of the spinning solution as 100%), the luminescent layer could only withstand 0.4MPa stress and the strain was only 52%. Therefore, the luminescent powder content should be below 31.6% (based on the total weight of the spinning solution as 100%), and the best effect was achieved when the luminescent powder content was in the range of 21.7%-27.0%.
[0094] Attached Figure 5 The rheological test diagram of the spinning solution with a luminescent powder content of 15.6% and 31.6% (based on the total weight of the spinning solution as 100%) (Supplementary Example 2) is shown in Figure 2. The spinning solution with a luminescent powder content of 31.6% (based on the total weight of the spinning solution as 100%) has a shear rate of 80s -1 The sudden shear thickening is not conducive to electrospinning, which further proves that the luminescent powder content should be below 31.6% (based on the total weight of the spinning solution as 100%).
[0095] Attached Figure 6 The stress-strain test diagram comparing electrospinning and thermal curing processes (Supplementary Examples 1 and 3) shows that when the content of the luminescent layer is the same, the luminescent layer prepared by electrospinning technology has significantly better strain than the luminescent layer prepared by thermal curing technology.
[0096] Attached Figure 7 This is a comparison picture of the ACEL device before and after stretching. It can be seen that the device can still work normally under 30% stretching deformation and the brightness does not change much.
[0097] Attached Figure 8 This is a brightness test of the ACEL device after repeated stretching 800 times under 30% tensile deformation. The device can still maintain 86.2% of the initial brightness after 800 stretchings.
[0098] Attached Fig. 9 This is a 72-hour brightness change diagram of the ACEL device in a double 85 (85°C temperature and 85% humidity) environment. As the test time increases, the brightness of the ACEL device increases first and then decreases. This is because some water molecules enter the device in the first 36 hours, increasing the conductivity between the two electrodes, resulting in an increase in the device brightness; and the aging of the device in the 36-72 hours is the aging of the device in this extreme environment, but it still maintains 89.3% of the initial brightness. This shows that the ACEL device still has good working stability in extreme environments.
[0099] Attached Fig.10 Schematic diagram of encapsulating ACEL device in elastic yoga clothing (Example 8), ACEL device maintains good stretchability when worn and fits the human body curve better. The luminous pattern is well displayed on the yoga clothing, and uniform luminescence can be observed under natural light conditions.
[0100] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0101] The above is a detailed introduction to the preparation of a flexible stretchable alternating current electroluminescent (ACEL) device and its preparation method by an electrospinning method provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a flexible and stretchable AC electroluminescent device, characterized in that The electroluminescent device comprises, from bottom to top, a bottom electrode, a light-emitting layer, a silver nanowire top electrode, and a PDMS encapsulation layer encapsulating the bottom electrode, the light-emitting layer, and the silver nanowire top electrode. The method comprises the following steps: S1 electrospinning to prepare a luminescent layer fiber membrane: dissolving an elastic polymer in an appropriate amount of an organic solvent, adding luminescent powder and barium titanate, stirring evenly to obtain a spinning solution, and using the spinning solution to electrospin to obtain a fiber membrane with a thickness of 100-200 μm, the fiber membrane is used as the luminescent layer of the device; Based on the total weight of the spinning solution as 100%, the content of barium titanate nanoparticles in the spinning solution is 5%-7%, the content of the luminescent powder is 15%-35%, the content of the polymer is 15-20%, and the balance is an organic solvent; S2 mask production: Design the luminous pattern on the computer and cut it with a plotter to obtain the mask for coating and printing the liquid metal bottom electrode; S3: Preparation of patterned liquid metal bottom electrode: attaching a mask to the light-emitting layer prepared in S1, and coating liquid metal on the surface of the light-emitting layer not covered by the mask to form a patterned liquid metal bottom electrode; S4: spray-printing silver nanowire top electrode: spray silver nanowire dispersion evenly on the side of the light-emitting layer prepared in S1 that is not coated with liquid metal, and dry it at room temperature to form a transparent top electrode; S5 device encapsulation: Use transparent PDMS solution to evenly spray on the top and bottom of the device for encapsulation to obtain a flexible and stretchable alternating current electroluminescent (ACEL) device.
2. The preparation method according to claim 1, characterized in that: In S1, the electrospinning conditions were: spinning propulsion speed of 1.5 mL / h, distance from needle tip to receiving roller of 10 cm, and spinning voltage of 8-12 kV.
3. The preparation method according to claim 1, characterized in that: In S1, the elastic polymer is selected from one or more of polyurethane (TPU), styrene (SBS), polydimethylsiloxane (PDMS) or polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); The luminescent powder is selected from one of the metal sulfide luminescent powders ZnS, CaS, SrS, CaGa2S4, SrGa2S4, and (Zn, Cd)S:Cu.
4. The preparation method according to claim 1, characterized in that: In S1, the organic solvent is selected from one of N,N-dimethylformamide (DMF) and tetrahydrofuran (THF), or a mixture of the two.
5. The preparation method according to claim 1, characterized in that: In S2, the mask is a cardboard without primer.
6. The preparation method according to claim 1, characterized in that: In S3, the liquid metal is one or more of gallium-indium alloy, gallium-tin alloy, gallium-indium-tin alloy, gallium-zinc alloy, gallium-rubidium alloy or gallium-cesium alloy.
7. The preparation method according to claim 1, characterized in that: In S1, based on the total weight of the spinning solution as 100%, the content of barium titanate nanoparticles in the spinning solution is 5%-7%, the content of the luminescent powder is 21.7%-32%, the content of the polymer is 15-20%, and the balance is the organic solvent.
8. The preparation method according to claim 1, characterized in that: In the spinning solution of S1, the content of luminescent powder is 21.7%-27%.
9. The preparation method according to claim 1, characterized in that: In S1, the thickness of the light-emitting layer is 160 μm±10 μm.
10. A flexible and stretchable alternating current electroluminescent (ACEL) device prepared according to the preparation method of claim 1.
Citation Information
Cited By
ZnS-coated PeSiO2 alternating-current electroluminescent fiber and preparation method thereof
CN122358354A
